The Political Cost of Lockdown's Enforcement - Andrea Fazio; Tommaso G. Reggiani; Fabio Sabatini (Institute of Labor Economics (IZA), 2021)
We study how the political cost of enforcing a lockdown in response to the COVID- 19 outbreak relates to citizens' propensity for altruistic punishment in Italy, the early epicenter of the pandemic. Approval for the government's management of the crisis decreases with the amount of the penalties that individuals would like to see enforced for lockdown violations. People supporting stronger punishment are more likely to consider the government's reaction to the pandemic as insufficient. However, after the establishment of tougher sanctions for risky behaviors, we observe a sudden flip in support for government. Higher amounts of the desired fines become associated with a higher probability of considering the government's policy response as too extreme, lower trust in government, and lower confidence in the truthfulness of the officially provided information. Lock-downs entail a political cost that helps explain why democracies may adopt epidemiologically suboptimal policies.
Keywords: D12; D83; I12; K40; 330; COVID-19; lockdown; law enforcement; altruistic punishment; incumbent support; trust in institutions; Italy